Isolation and diagnosis of fungi associated with sesame seeds - Faten Al-Refaee (College of Education for Pure Sciences, 2005)
This study was conducted for the purpose of finding sesame seed borne fungi which produce the Lipase . Forty different isolates were obtained from different regions of Iraq (Baghdad , Slah-Al.Dan , Babylon , Taamim , Al.Anbar and Ninevah), The percentage isolate of Rhizopus stolonifer and Aspergillus niger was Found to be (22 and 20 %) respectively from Ninavh seed , and 14 % Q? Altemaria sesami from Al-Anbar. Aqualitative test was conducted to clieck the capabilities of these isolates to produce the Lipase in solid cultures and to find the most active fungi producing the enzyme , It was found that all isolates produced lipase except Rhizoctnia solani and Fusari.um sp. Isolated from Baghdad and Babylon respectively .